2004
DOI: 10.1203/01.pdr.0000112244.72924.26
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Airway Inflammation after Resolution of Respiratory Syncytial Virus Infection in Rats

Abstract: Neurogenic inflammation is markedly potentiated in airways that are infected with respiratory syncytial virus (RSV). Aims of this study were to determine whether this potentiation persists after the virus is cleared, investigate the mechanism of postviral potentiation, and define whether prophylaxis with a MAb against the RSV fusion protein (palivizumab) prevents this effect. Thirty days after inoculation, no evidence of active RSV infection was found in the airway epithelium by plaque assay or immunostaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 27 publications
4
31
0
2
Order By: Relevance
“…RSV was discovered more than 50 years ago and continues to be a chief cause of hospitalization worldwide, not only in infants, but also in older and high-risk adults (3). RSV infection in childhood has been linked to chronic inflammation and asthma (40)(41)(42), and although we have a very detailed understanding of RSV immunopathogenesis (43)(44)(45)(46)(47), current treatment strategies for RSV infection are largely supportive. Palivizumab, which is approved for RSV prophylaxis in high-risk infants, has only moderately decreased hospital admission due to RSV infection (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…RSV was discovered more than 50 years ago and continues to be a chief cause of hospitalization worldwide, not only in infants, but also in older and high-risk adults (3). RSV infection in childhood has been linked to chronic inflammation and asthma (40)(41)(42), and although we have a very detailed understanding of RSV immunopathogenesis (43)(44)(45)(46)(47), current treatment strategies for RSV infection are largely supportive. Palivizumab, which is approved for RSV prophylaxis in high-risk infants, has only moderately decreased hospital admission due to RSV infection (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the local irritation of C-type nociceptive afferents in infected airways evokes bronchospasm, neurogenic inflammatory edema, and recruitment and activation of leukocytes (10). We showed previously that RSV infection amplifies the inflammatory and immunomodulatory effects of sensory nerves via both presynaptic (increased synthesis and release of substance P) and postsynaptic [up-regulation of neurokinin 1 (NK 1 ) receptors] mechanisms (11)(12)(13), both involving the overexpression of nerve growth factor by the infected respiratory epithelium (14).…”
mentioning
confidence: 99%
“…Similarly, a specific NK1 receptor antagonist abolished the recruitment of both lymphocytes and monocytes to infected airways thereby reducing the local inflammatory response (14). Recently a study done in rats showed that administration of palivizumab 24 h before virus inoculation prevented the development of abnormal neurogenic inflammatory responses (22). Taken together, such interventions may prove beneficial in children with OSA in the future, and may be applicable to other highly prevalent respiratory viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Neurogenic inflammation within AT tissues, as suggested in our study, has been previously studied in an animal model of asthma. Neurogenic inflammation was markedly potentiated in the lower airways of rats that were infected with RSV long after the virus was cleared from the airway (22). Thus, the presence of a RSV-initiated inflammatory process appeared to be mediated by the high affinity receptor for substance P (NK1 receptor), the expression of which is greatly increased following inoculation with RSV (21).…”
Section: Discussionmentioning
confidence: 99%